(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2019)
This article discusses the group of thirty-eight inscribed manumission documents, emanating from the Kabeirion in north-east Lemnos. This corpus is of a great importance for the study of the island, its Athenian and other population, and the role of the sanctuary and the cult celebrated there, as well as to the study of manumission. While the work done by scholars who studied the inscriptions has shed light on this lesser-known site of manumission, thus adding valuable information to what is known on manumission practices and manumission documents in the Greek world, there are some important questions related to this corpus that still remain to be elucidated. In this article I will briefly review the main features of these manumission documents that emerge from previous studies and consider in greater detail the questions that remain unsolved, suggesting some answers where such can be given.